Impact Assestement of Cultural Events on Tourism and Creative Economy Sector: A Case Study of Dieng Creative Festival - Wawan Rusiawan; Sinar Wijayanti (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
This study explores the Dieng Creative Festival (DCF) management strategies that combine tourism and traditional ceremonies, emphasising community-based tourism (CBT) and collaboration for sustainable and independent festival management to benefit citizens. Qualitative ethnographic methods are used in this study to reveal the meaning of a culture by interpreting objects, stories, rituals, and practices in a cultural group. The results of the survey show that DCF can have a significant impact on the tourism and creative economy sectors if the event organisers implement the following strategy: DCF organisers need to determine the orientation of the organisation in the form of increasing the tourism industry economy; preserving local traditions; and synergy between the two. The orientation of the DCF implementation aims to align the needs of preserving tradition and increasing the tourism economy, it is necessary to involve residents in its planning and implementation. Resident participation is closely related to efforts to preserve living traditions. DCF organisers need to determine the target audience for their festival. Festival development can be directed by building a strategy for packaging events, promotions, implementation schedules, attractions, amenities, and other supporting hospitality facilities. DCF has provided business opportunities for small business actors. Festival organisers need to provide access to MSMEs and increase their equality. The government is advised to be a catalyst for implementing sustainable festivals. In addition to funding support for DCF, the government needs to provide space and facilities that bring together festival organisers, including residents, business actors, academics, and the media. This space can be helpful for organisers to learn and network to improve the festival's quality